2002
DOI: 10.1093/toxsci/68.1.249
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Toxicity Studies on Perfluorooctanesulfonate Potassium Salt in Cynomolgus Monkeys

Abstract: This study was conducted to determine the earliest measurable response of primates to low-level perfluorooctanesulfonate (PFOS) exposure and to provide information to reduce uncertainty in human health risk assessment. Groups of male and female monkeys received 0, 0.03, 0.15, or 0.75 mg/kg/day potassium PFOS orally for 182 days. Recovery animals from each group, except the 0.03 mg/kg/day dose group, were monitored for one year after treatment. Significant adverse effects occurred only in the 0.75 mg/kg/day dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
331
7
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(359 citation statements)
references
References 32 publications
10
331
7
7
Order By: Relevance
“…Exposure to PFOS caused a reduction in serum T4 and T3 in rats and mice [18], and a decrease in serum T3 and estradiol levels in monkeys [27]. However, the mechanism of thyroid disruption still needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to PFOS caused a reduction in serum T4 and T3 in rats and mice [18], and a decrease in serum T3 and estradiol levels in monkeys [27]. However, the mechanism of thyroid disruption still needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effect levels have been determined for PFOS in the serum of cynomolgus monkeys [40]. The blood of the present polar bears has also been analyzed (Supplemental Data, Table S6), and with that, we may be able to more easily compare how close current concentrations are to adverse effect levels.…”
Section: Possible Toxicological Implicationsmentioning
confidence: 99%
“…Comparatively, PFOA has a faster rate of elimination than PFOS in rats, as well as other animals and even humans. For both genders of cynomolgus monkeys, an elimination half-life of about 20-30 days was found following dosing with PFOA , while a half-life of approximately 100-200 days was determined after exposure to PFOS (Seacat et al 2002). Based on recent monitoring of retired production workers, it has been demonstrated that both these perfluorochemicals have a relatively longer serum elimination half-life in humans (4.4 ± 3.6 years for PFOA vs. 8-9 years for PFOS) than in most mammals (Burris et al 2002;Olsen et al 2007).…”
Section: Comparison Of Elimination Of Pfoa Versus Pfos In Ratsmentioning
confidence: 99%
“…Increasing numbers of studies have indicated the toxic effects caused by this kind of peroxisome proliferators in exposed laboratory animals (Seacat et al 2002;2003). PFOA and PFOS caused reductions in body weight, decreases in weight gain rate, and interference in lipid metabolism in rats (Lau et al 2007;Luebker et al 2002).…”
mentioning
confidence: 99%